New records of the giant planarian Polycladus gayi Blanchard, 1845 (Platyhelminthes: Geoplanidae) with notes on its conservation biology - Barahona-Segovia, Rodrigo M.; Araya, Juan Francisco; Pañinao-Monsálvez, Laura (Zootaxa, 2020)
Land planarians (Tricladida:Geoplanidae) comprise about 910 species distributed in four subfamilies and can be found on all continents except Antarctica (Sluys & Riutort 2018; Sluys 2019). The Neotropical region possesses nearly 31% of all the described terrestrial planarian species, most of them belonging to the subfamily Geoplaninae (Sluys 1999; Grau & Carbayo 2010). Land planarians are mostly habitat-specialists, living in the humid soils of native forest, and predating on invertebrates like earthworms, isopods, mollusks and harvestmen, among others (Ogren 1995; Carbayo & Leal-Zanchet 2003; Boll & Leal-Zanchet 2016). Although most planarian species seem to be physiologically sensitive, for example to environmental moisture, a few land planarian genera like Bipalium Stimpson and Obama Carbayo et al., have successfully invaded many habitats, even in highly perturbed areas (Kawaguti 1932; Sluys 2019). Therefore, some of these invertebrate species appear to be good candidates as habitat quality bioindicators according to some authors (Sluys 1998; Gerlach et al., 2013; Negrete et al., 2014).